1993
DOI: 10.1002/ana.410340313
|View full text |Cite
|
Sign up to set email alerts
|

The T‐cell response to myelin basic protein in familial multiple sclerosis: Diversity of fine specificity, restricting elements, and T‐cell receptor usage

Abstract: Indirect evidence suggests that an autoimmune response to myelin basic protein (MBP) may be involved in the pathogenesis of multiple sclerosis (MS). In MS, several reports have suggested that restricted T-cell populations respond to MPB, as in inbred rodents with the MS disease model experimental allergic encephalomyelitis. In experimental allergic encephalomyelitis, the T-cell repertoire to MBP varies between strains, and in MS it is likely that the response to MBP is also best defined under conditions where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 58 publications
4
28
0
Order By: Relevance
“…The frequency of MBP-reactive T cell clones in circulat- ing PBMC of normal C. jacchus ranged between 3 and 7 per lo-, similar to the frequency estimated to be present in the circulation of healthy humans (8)(9)(10)(11)(12). Mapping of the antigenic peptides recognized by individual clones indicated that multiple regions of the MBP molecule were recognized by naturally occurring T cells (Fig.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The frequency of MBP-reactive T cell clones in circulat- ing PBMC of normal C. jacchus ranged between 3 and 7 per lo-, similar to the frequency estimated to be present in the circulation of healthy humans (8)(9)(10)(11)(12). Mapping of the antigenic peptides recognized by individual clones indicated that multiple regions of the MBP molecule were recognized by naturally occurring T cells (Fig.…”
Section: Resultssupporting
confidence: 66%
“…They were similar in several respects to the repertoire of circulating MBP-reactive cells described in human blood (8)(9)(10)(11)(12). First, circulating MBP-reactive T cells occur at similar frequencies in the two species.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In contrast to MOG, relatively low frequencies of MBP-reactive T cells, generally in the range of 10 Ϫ5 -10 Ϫ6 , have been described by traditional limiting dilution methods in MS patients (31,32,68). A similar low frequency has been reported against another quantitatively major myelin protein, proteolipid protein (32).…”
Section: Discussionmentioning
confidence: 89%
“…Two hydrophilic regions of PLP, residues 30-49 and 180-199, were recently demonstrated to be immunodominant regions recognized by human peripheral T cell populations after primary in vitro stimulation with native PLP (33). However, results from several laboratories have further revealed a marked heterogeneity of human T cell proliferative responses to MBP and PLP with respect to epitope recognition, MHC restriction, and T cell receptor usage (13, 28,30,[34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Furthermore, there is evidence for progressive diversification of the T cell repertoire during the course of autoimmune disease.…”
Section: Introductionmentioning
confidence: 99%